El estudio académico de lo esotérico - Chaves Pacheco, José Ricardo (2015)
This article is divided into two parts. First, it analyzes the linguistic and historical development of the esoteric and esotericism concepts, processes that evolved an incipient “historical consciousness” among the esotericists, influenced by the romantic historicist flow, which formed a new type of esotericism in times of science, democracy and modernity. Second, the article explains the process of disciplinary transformation of the study of esoterica, esotericism and esoterology until the imposition of the academic category of “Western Esotericism Studies”.